Victory at Entebbe they considered every possibility - and then did the impossible! - Berger, Helmut 1944-2023; Blair, Linda; Douglas, Kirk 1916-2020; Chomsky, Marvin J. 1929-2022 (Warner Home Video, 2012)
An Air France airplane is hijacked by the PLO due the large number of Israeli and Jewish passengers. We follow the action both with the hostages as they cope with confinement and threatened death, and the Israeli cabinet and military that must try to get them out. (Written by David Carroll for IMBb)
Orig.: USA 1976